Recognition of Tuberous Sclerosis in Adult Women: Delayed Presentation With Life-Threatening Consequences - Seibert, Diane (2011)
BACKGROUND: Tuberous sclerosis complex (TSC) is associated with tumor development in the brain, retina, kidney, skin, heart, and lung. Seizures, intellectual disability, and characteristic skin lesions commonly manifest in early childhood, but some findings, notably renal angiomyolipomas and pulmonary lymphangioleiomyomatosis (LAM), emerge later, placing adults with undiagnosed TSC at increased risk for morbidity and mortality. OBJECTIVE: To describe the clinical presentation and severity of TSC in adult women. DESIGN: Retrospective cohort study. SETTING: National Institutes of Health Clinical Center, Bethesda, Maryland, 1995 to 2010. PATIENTS: 79 women aged 18 years or older who were enrolled in an observational cohort study of TSC to evaluate disease manifestations. MEASUREMENTS: History, physical examination, pulmonary function testing, chest radiography, abdominal computed tomography, high-resolution chest computed tomography, and brain magnetic resonance imaging were used to evaluate patients. RESULTS: Among the 45 patients who received a diagnosis of TSC in adulthood, 21 presented with symptoms due to LAM, 19 with renal angiomyolipomas, and 10 with seizures. Of the 45 patients, 30 met clinical criteria for TSC in childhood that remained undiagnosed for a median of 21.5 years and 15 were older than 18 years before meeting the clinical criteria for TSC. Patients diagnosed in adulthood and those diagnosed in childhood had similar occurrences of pneumothorax, shortness of breath, hemoptysis, nephrectomy, and death. LIMITATION: No men were included in the study, and selection was biased toward patients having pulmonary LAM. CONCLUSION: Women who received a TSC diagnosis in adulthood had minimal morbidity during childhood but were still at risk for life-threatening pulmonary and renal manifestations. PRIMARY FUNDING SOURCE: Intramural Research Program, National Institutes of Health, National Heart, Lung, and Blood Institute.